Patriarchy and Womens Subordination: A Theoretical Analysis - Sultana, Abeda (Arts Faculty Journal, 2012)
Patriarchy is the prime obstacle to womens advancement and development. Despite differences in levels of domination the broad principles remain the same, i.e. men are in control. The nature of this control may differ. So it is necessary to understand the system, which keeps women dominated and subordinate, and to unravel its workings in order to work for womens development in a systematic way. In the modern world where women go ahead by their merit, patriarchy there creates obstacles for women to go forward in society. Because patriarchal institutions and social relations are responsible for the inferior or secondary status of women. Patriarchal society gives absolute priority to men and to some extent limits womens human rights also. Patriarchy refers to the male domination both in public and private spheres. In this way, feminists use the term patriarchy to describe the power relationship between men and women as well as to find out the root cause of womens subordination. This article, hence, is an attempt to analyse the concept of patriarchy and womens subordination in a theoretical perspective. DOI: http://dx.doi.org/10.3329/afj.v4i0.12929 The Arts Faculty Journal Vol.4 July 2010-June 2011 pp.1-18